2022
DOI: 10.3390/ph15020192
|View full text |Cite
|
Sign up to set email alerts
|

SAMe, Choline, and Valproic Acid as Possible Epigenetic Drugs: Their Effects in Pregnancy with a Special Emphasis on Animal Studies

Abstract: In this review, we discuss the functions and main effects on pregnancy outcomes of three agents that have the ability to induce epigenetic modifications: valproic acid (VPA), a well-known teratogen that is a histone deacetylase inhibitor; S-adenosylmethionine (SAMe), the most effective methyl donor; and choline, an important micronutrient involved in the one methyl group cycle and in the synthesis of SAMe. Our aim was to describe the possible effects of these compounds when administered during pregnancy on the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
15
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
2
1

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(15 citation statements)
references
References 139 publications
0
15
0
Order By: Relevance
“…Therefore, we extended our study by using the teratogens ISO, VPA and THD and the non-teratogen BSP to identify speci c cardiomyogenic gene signature/pathways by performing transcriptome analysis at the different stages of differentiation, combined with testing of functional alterations during CMs contractions. It is well known that the teratogen THD causes malformations of the limbs [32] whereas VPA induces congenital malformations and is a neurological teratogen [33,34].…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, we extended our study by using the teratogens ISO, VPA and THD and the non-teratogen BSP to identify speci c cardiomyogenic gene signature/pathways by performing transcriptome analysis at the different stages of differentiation, combined with testing of functional alterations during CMs contractions. It is well known that the teratogen THD causes malformations of the limbs [32] whereas VPA induces congenital malformations and is a neurological teratogen [33,34].…”
Section: Discussionmentioning
confidence: 99%
“…2,3 Lacosamide shares with valproate the ability to induce histone hyperacetylation, which has been suggested as a mechanism of valproate teratogenicity. 4,5 However, the effects of valproate and lacosamide on histone acetylation are mediated by distinct mechanisms. [6][7][8] In a series of in vitro, ex vivo, and in vivo studies, we have consistently demonstrated that the placenta is an important target of antiseizure medications (ASMs).…”
Section: Introductionmentioning
confidence: 99%
“…Over the past years, lacosamide has been increasingly prescribed as an add‐on treatment for pregnant women, although its teratogenicity potential and its neurodevelopmental effects have not been clearly established 2,3 . Lacosamide shares with valproate the ability to induce histone hyperacetylation, which has been suggested as a mechanism of valproate teratogenicity 4,5 . However, the effects of valproate and lacosamide on histone acetylation are mediated by distinct mechanisms 6–8 …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, SAMe concentrations were also reduced in rat brain tissue following treatment with monoamine reuptake inhibitors [ 12 ]. SAMe was also suggested to be a potent epigenetic drug [ 8 , 13 ].…”
Section: Introductionmentioning
confidence: 99%